solve by formula method
Attachments:
![](https://hi-static.z-dn.net/files/d70/54978846939690ab925385c4dd7444d7.jpg)
Answers
Answered by
0
Answer:
the formula is ax^2+bx+c.
Step-by-step explanation: So the sums can be converted in this formula and be solved by middle term spilitting
eg-
in 2)-4x^2+9x+1 that is conversion then solving.
aniketjadhav45:
solution
Answered by
0
Answer:
1) 2x²+x-1/5 = 0
multiply the given equation by 5
2x²×5 + x-1/5×5 =0
10x²+x-1 = 0
comparing with ax²+bx+c=0
a = 10 , b = 1 , c= -1
b²-4ac = 1²-4×10×-1
= 1 +40
=41
x = -b+-√b²-4ac /2a
= -1√41/2×10
= -1 +-√41/20
2) 9x+1=4x²
4x²-9x-1=0
comparing with ax²+bc+c=0
a=4 , b=-9 ,c= -1
b²-4ac = -9²-4×4×-1
= 81+16
= 91
x= -b+-√b²-4ac/2a
= -(-9) +-√91/2×4
= 9+-√91/8
3) 2x²+5x-2=0
comparing with ax²+bx+c=0
a=2 ,b=5 , c = -2
b²-4ac= 5²-4×2×-2
= 25+16
= 41
x= -b+-√b²-4ac/2a
= -5+-√41/2×2
= -5+-√41/4
Similar questions